45.2k views
0 votes
HELPPPPPPPPPPP MEEE PLS

HELPPPPPPPPPPP MEEE PLS-example-1

1 Answer

1 vote

Answer:

See explanation below

Explanation:

If the base of a radical exponent is the same then the following properties hole and x≠ 0


\sqrt[n]{x} =
x^{(1)/(n) Rule 1


(x^m)/(x^n) = x^(m-n) Rule 2


(x^m)^n = x^(mn) Rule 3

The numerator in the expression is


\sqrt[3]{x^2y^5} =(x^2)^(1)/(3) (y^5)^(1)/(3) = x^(2)/(3)} . y ^ (5)/(3) Using rules 1 and 3

The denominator is


\sqrt[4]{x^3y^4} =(x^3)^(1)/(4) (y^4)^(1)/(4) = x^(3)/(4)} . y ^ 1} Using rules 1 and 3

Therefore the original expression in exponent form is


(x^(2)/(3) y ^ (5)/(3))/(x^(3)/(4) y ^ 1)}

Using rule 2 we get the final expression as


x^{(2)/(3)-(3)/(4)}$ $y^{(5)/(3)-1}

2/3 - 3/4 = 8/12 - 9/12 = -1/2

5/3 - 1 = 5/3 - 3/3 = 2/3

So the final expression is


$x^{-(1)/(12)}y^{(2)/(3)}$

Proved

User Nbayly
by
5.4k points